-1-7x+42+1x=36

Simple and best practice solution for -1-7x+42+1x=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1-7x+42+1x=36 equation:



-1-7x+42+1x=36
We move all terms to the left:
-1-7x+42+1x-(36)=0
We add all the numbers together, and all the variables
-6x+5=0
We move all terms containing x to the left, all other terms to the right
-6x=-5
x=-5/-6
x=5/6

See similar equations:

| 2^2x-3+52=180 | | -7x-2x+9=18 | | -4(x+5)=(x-4) | | -5a+6a=-5 | | 5x+1+3x+4+2x+5=2x+x+13 | | 44+4(8=h) | | 16x-1=-5+15x | | 6x+200=-6x+50” | | 20x-18=-7 | | 7n-11=5n7 | | x^2-48x-8960=0 | | 2.r+11=-4.9r+29 | | 5x+16=2x+3 | | -12=10x+6x+4 | | 7n-11=5n-7 | | 10/21n=7/6 | | -k+-18=-5-k-13 | | 3(c+5)-5=-5 | | 4x-0.8=-12.6 | | 5.8=10x+3.8 | | 7=7x-17-5x | | 7-(3x+5)=5x+12 | | -7v+8v=-6 | | 7-(3x+5)=5x12 | | 5x-10=7x=28 | | 2y=75-y | | 3x^2-12x-54=-3 | | 7-(3x+5)=5x=12 | | 13=g3+4 | | 14.25=x-29.15 | | 7x-20=-14 | | 9x-58.4=x |

Equations solver categories